2011
DOI: 10.1016/j.proeng.2011.04.341
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Sandwiches for Civil Applications

Abstract: Physics and mechanical tests were carried out on innovative sandwiches proposed for civil applications, at the aim to know their performances. The core was obtained by embedding short mineral fibre, in different percentages, in polyurethane matrix. The results of the experimental tests were compared to what obtained on sandwiches made without any reinforcement in the polyurethane core: better behaviours were found in terms of compression strength and elastic modulus, compression energy absorption capability, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Varying k 0 until the straight line best fitting the data in the diagram will pass through the origin. In Lopresto et al, 5 this condition was found for GFRP with values of k 0 ¼1.06 mm and c 0 ¼0.931, which were insensitive to t and the diameter of the indenter, D i .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Varying k 0 until the straight line best fitting the data in the diagram will pass through the origin. In Lopresto et al, 5 this condition was found for GFRP with values of k 0 ¼1.06 mm and c 0 ¼0.931, which were insensitive to t and the diameter of the indenter, D i .…”
Section: Introductionmentioning
confidence: 83%
“…A modified model 5 for the prediction of the indentation was assessed in the present case. A correlation between the dent depth and the absorbed energy was studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite sandwich structures, often consisting of two strong skin sheets and one layer of soft core, are becoming increasingly popular in aerospace, automotive and construction industry owing to their very high performance to weight ratio. Numerous studies were conducted to study the mechanical properties as well as the failure mechanisms of different types of sandwich structures theoretically and experimentally by researchers in different areas [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Using composite sandwich structures as secondary components, such as curtain walls, is one of the most promising areas in the building and construction industry. Most of the composite sandwich panels that were studied in the published literature have two common features [5][6][7][8][10][11][12]: (a) the cross section of the panel is symmetric, and (b) the skin of the panel is most likely to be fibre-reinforced polymer (FRP) or concrete. However, because a curtain wall is the main non-structural component that separates the indoor environment of a building from outdoor, the service condition is particularly different from that of either indoor or outdoor.…”
Section: Introductionmentioning
confidence: 99%